Longitudinal assessment of lung area measurements by two‐dimensional ultrasound in fetuses with isolated left‐sided congenital diaphragmatic hernia. (19th March 2015) - Ruano, R.; Britto, I. S. W.; Sangi‐Haghpeykar, H.; Bussamra, L. C. S.; Da Silva, M. M.; Belfort, M. A.; Deter, R. L.; Lee, W.; Tannuri, U.; Zugaib, M.
ABSTRACT: Objective: To evaluate lung growth in healthy fetuses and those with congenital diaphragmatic hernia (CDH) using two‐dimensional (2D) ultrasound. Methods: Fetal right lung measurements obtained by 2D ultrasound between 19 and 37 weeks' gestation were evaluated longitudinally in 66 healthy fetuses and 52 fetuses with isolated left‐sided CDH. Right lung areas were determined by the 'tracing' and 'longest‐diameters' methods and, subsequently, lung area‐to‐head circumference ratios (LHRs) were calculated. Functions fitted to these size parameters with respect to gestational age were evaluated for three sets of group‐wise comparisons: (1) healthy vs CDH fetuses; (2) different degrees of severity of CDH; and (3) CDH fetuses that survived vs those that died by 6 months postpartum. Results: There was a significantly slower increase in right lung areas and LHRs with advancing gestational age in CDH fetuses than in healthy individuals ( P < 0.05). Compared to those with milder forms of CDH, lung areas and LHRs of fetuses with more severe forms displayed a smaller increase ( P < 0.05) and LHRs of fetuses with severe CDH did not increase during pregnancy ( P > 0.05). Individuals who died postpartum did not show any increase in LHR ( P > 0.05) throughout gestation. Conclusions: The right lung area and LHR, calculated using either the longest‐diameters or tracing method, display reduced growth rates during gestation in cases of isolated left‐sided CDH as compared with healthy fetuses. The growth curve characteristics of fetal lung areas and LHRs may be useful for predicting neonatal mortality. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.